Construction and Validation of Attraction for Morbid Events Multifactor Scale - Plutarco, Lia Wagner (2021)
Objective. This study aimed to construct and validate the Attraction for Morbid Events Multifactor Scale (EMAEM). Method. Two empiric studies were conducted. 252 people from the general population participated in the first study, in which a main component analysis was conducted to attest the factor structure of EMAEM. In this study, the five-factor model was most suitable. In the second study, the participants were 609 people from the general population that answered personality and antisocial behavior scales, besides EMAEM. Results. Confirmatory Factor Analysis shows the suitability of the five-factor model. Moreover, the EMAEM scale can provide aids to a better understanding of personality traits associated with engaging in risky behavior.